Graphene-based thermionic-thermoradiative solar cells: Concept, efficiency limit, and optimum design. (1st January 2020) - Zhang, Xin; Ang, Yee Sin; Du, Jian-Ying; Chen, Jincan; Ang, Lay Kee
Abstract: Solar energy conversion to electricity usually adopts two main methods: photovoltaic and solar-thermal power generation. Here, graphene-based thermionic-thermoradiative solar cells are expanded to include photovoltaics based on thermionic-thermoradiative converters, hybrid concept, efficiency limit, and optimum design. For realistic and practical design, a comprehensive and consistent model is formulated to include effects of thermal coupling between the absorbers, space-charge effect, non-radiative recombination, and various irreversible energy losses. By combining thermionic emission and thermoradiative mechanisms, thermionic-thermoradiative solar cells make use of electron and photon fluxes simultaneously to efficiently convert solar radiation to electricity, and thus enable a significant improvement in terms of heat utilization and conversion efficiency. Based on the calculated results, optimum choices of materials and the parametric design strategies of the system are determined. The findings predict a high solar-to-electricity efficiency of 0.225 in using a graphene-caesiated tungsten graphene-based thermionic energy converter and an Aluminium-32 gallium-48 arsenide-based thermoradiative cell under 800 sun irradiance. This work also demonstrates the importance of recycling waste heat for performance optimization and opens up new avenues to boost the overall conversion efficiency of such systems. Graphical abstract: The graphene-based thermionic-thermoradiative solar cell with a stacked structure by combining thermionic emission and thermoradiative mechanisms, to efficiently convert solar radiation to electricity. Here graphene is used as the cathode (emitter) to improve the capacity of electron emission attributing to its unique advantages, such as excellent mobility, high thermal stability (up till 4000 K), and superior thermal conductivity. Image 1 Highlights: The proposed solar cell yields an efficiency of 0.225 under 800 sun irradiance. Performances of the system are greatly improved compared to subcomponents. Reduced space charge effect and recombination loss provide better performance. Maximum conversion efficiencies are sensitively controlled by solar concentrations. The results pave the way for the development of low-cost high-performance solar cells.